2023
DOI: 10.1186/s12887-023-04177-w
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine knowledge and conspiracy beliefs among secondary school students in Lebanon

Abstract: Background Human Papillomavirus (HPV) is widely prevalent across the globe. In Lebanon, the society is transitioning from traditional conservatism to a more open attitude. Although previous studies have examined the knowledge of adults in Lebanon with regard to HPV and its vaccine, there is a lack of research on secondary school students. Moreover, HPV is considered a worldwide public health matter that needs to be addressed. Therefore, the objective of our study is to assess factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A 2019 review looking at studies from Iran showed that overall population knowledge of HPV vaccine was low but attitude towards the vaccine tended to be positive; the only study from the review that looked at parental attitude towards the vaccine showed that 76% of parents had no knowledge about HPV infection [ 32 ]. In a recent study from Lebanon only 11.3% of students 15–18-year-old reported receiving at least one dose of HPV vaccine, 36.5% were not sure if they had received any doses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 review looking at studies from Iran showed that overall population knowledge of HPV vaccine was low but attitude towards the vaccine tended to be positive; the only study from the review that looked at parental attitude towards the vaccine showed that 76% of parents had no knowledge about HPV infection [ 32 ]. In a recent study from Lebanon only 11.3% of students 15–18-year-old reported receiving at least one dose of HPV vaccine, 36.5% were not sure if they had received any doses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most stated reasons for non-acceptance of HPV vaccine in our study were the lack of knowledge and provider recommendation, both of which may be related as doctors are expected to educate patients about the vaccine when recommending it and since physicians were reported as an entrusted source of medical information. Only 21.9% of Lebanese secondary school students reported hearing about the HPV vaccine from their doctor, whereas internet was their primary source of knowledge (48%) [ 33 ]. This may be due to a lack of knowledge of primary care physicians about the vaccine or lack of empowerment in recommending the vaccine.…”
Section: Discussionmentioning
confidence: 99%